The effect of dexmedetomidine on expression of neuronal nitric oxide synthase in spinal dorsal cord in a rat model with chronic neuropathic pain - Jun Pang; Suming Zhang; Ying Kong; Zhe Wang; Ruomeng Pei; Ping Zhuang; Xiaopeng Wang (Arquivos de Neuro-Psiquiatria)
Background Neuropathic pain typically refers to the pain caused by somatosensory system injury or diseases, which is usually characterized by ambulatory pain, allodynia, and hyperalgesia. Nitric oxide produced by neuronal nitric oxide synthase (nNOS) in the spinal dorsal cord might serve a predominant role in regulating the algesia of neuropathic pain. The high efficacy and safety, as well as the plausible ability in providing comfort, entitle dexmedetomidine (DEX) to an effective anesthetic adjuvant. The aim of this study was to investigate the effect of DEX on the expression of nNOS in spinal dorsal cord in a rat model with chronic neuropathic pain.